Acupuncture and Cardiovascular Disease: Focus on Heart Failure. Issue 2 (March 2018) - Ni, Yu-Ming; Frishman, William H.
Abstract : Symptomatic heart failure is managed with interdisciplinary approaches to reduce acute exacerbations and to improve mortality. Acupuncture is a standardized treatment of Traditional Chinese Medicine that has been shown to have beneficial effects on the cardiovascular system via a neurohumoral pathway known as the long-loop pathway. This article serves to examine recent evidence supporting the long-loop pathway as the physiologic mechanism of acupuncture and the sympatholytic, vasodilatory, and cardioprotective effects of acupuncture that could specifically improve cardiac function and quality of life measures in the management of congestive heart failure.